Surgical debridement as a Treatment for Corneal Ulcer due to Gasoline - Gyabrina, Asifa; Dwiputra, Pardana; Wara Nandini, Pramadita (Universitas Airlangga, 2025)
Introduction: A Corneal ulcer is an ocular emergency that leads to blindness. It is caused by a defect in the corneal epithelium involving the underlying stroma. Even with prompt treatment, complications such as corneal scarring or perforation, glaucoma, cataract, anterior or posterior synechiae, and blindness may occur. Corneal ulcers can result from trauma or from a disease that allows bacteria or fungi to enter the cornea, leading to infection or inflammation. This study reports a case of a chemical-induced corneal ulcer that did not respond to medical therapy but healed after surgical debridement of the ulcer base. Case Presentation: An 18-year-old man with a history of a right eye chemical injury caused by gasoline. He was presented to the hospital with a complaint of burning in his right eye, blurred vision, watering, glare, and purulent discharge. His right eye slit lamp examination revealed a plaque on the central cornea measuring approximately 6 mm in diameter, with a feathery edge and no hypopyon in the anterior chamber. His visual acuity (VA) in the right eye is 1/60, and in the left eye is 6/8.5. Corneal scraping of the ulcer was sent for fungal culture and microscopy. The result showed Staphylococcus Haemolyticus, a gram-positive bacterium. He was diagnosed with a right eye corneal ulcer bacterial infection with a differential diagnosis of fungal infection. Previously, he had been given a combination of antibiotics and antifungal, and there was no clinical improvement after two weeks; therefore, debridement surgery was performed. VA improved after debridement surgery. The plaque diameter has decreased, and VA has improved. Conclusions: Corneal infection caused by multiple microorganisms is relatively uncommon. The most common risk factor for mixed bacterial and fungal corneal ulcer was ocular trauma. The treatment for a mixed bacterial and fungal corneal ulcer involves topical, systemic, and surgical debridement, with one-month follow-up. The surgical debridement was adequate in handling cases like this and can shorten the healing time of corneal ulcers, as shown by the increase in VA in the right eye from 1/60 to 2/60 at the last visit.